Nguyễn Văn Trường
Giới thiệu về bản thân
Chào mừng bạn đến với trang cá nhân của Nguyễn Văn Trường
0
0
0
0
0
0
0
2025-02-01 19:48:17
(A=\frac{x+2\sqrt{x}+1}{x\sqrt{x}+1}+\frac{1}{\sqrt{x}-2}-\frac{1}{x-4}) với (x\ge0) và (x\ne4) (A = \frac{(\sqrt{x}+1)^2}{(\sqrt{x}+1)(x-\sqrt{x}+1)} + \frac{1}{\sqrt{x}-2} - \frac{1}{(\sqrt{x}-2)(\sqrt{x}+2)}) (A = \frac{\sqrt{x}+1}{x-\sqrt{x}+1} + \frac{\sqrt{x}+2-1}{(\sqrt{x}-2)(\sqrt{x}+2)}) (A = \frac{\sqrt{x}+1}{x-\sqrt{x}+1} + \frac{\sqrt{x}+1}{x-4}) (A = (\sqrt{x}+1)(\frac{1}{x-\sqrt{x}+1} + \frac{1}{x-4}))